Дослідження технологічної схеми роботи водопідйомної установки типу ВУ - Василенков, В. Є.; Наземцев, О. В. (Енергетика і автоматика, 2017)
UDC 631.3:621.1RESEARCH WORK flowsheet lifting devices such as VUV.E. Vasilenkov, , A.V. Nazemtsev For lifting and distribution of water used pump installation, consisting of a receiving water, sewage treatment plants, potable water reservoirs or water towers, connecting water mains and electric stations of management. The most widely spread in agriculture centrifugal and axial pumps. They perform a monoblock with electric motors and immersed in water in the well pipe diameter 100 ...250 mm(submersible pumps) or placed on the ground. There are submersible pumps with electric motors located on the well. These pumps are called artesian.To lift water from open reservoirs and wells mine is also floating centrifugal pumps. Widespread so-called three-inertial vibration pumps with electromagnetic drive. These pumps have a small supply of water (up to 1 m3/h at pressures at20 m). The rural population uses them in everyday life.In agriculture using pump installation of three types: Water tower with tank water pumping installations accumulator with direct water supply to a water network. Almost 90% of the tower using pump installation of water flow up to 30 m3/h. If the water flow is 30 ... 65 m3/h, it is recommended dvohahrehatni pumping station with accumulator. When water flow over 65 m3/h economically feasible to use pumps with direct water supply distribution network (irrigation system).Noteworthy consideration flowsheet crazy auto-lifting BY installation type, which is designed to lift water from open water and mine pit depth of5 mat a pressure of 25 ...80 m.The purpose of the work. Consideration of crazy technological scheme of automatic lifting installation type clause for lifting water from open reservoirs and wells mine of small depths of up to 5m.Materials and methods of research. Systems and schemes of water supply, water pumping principles of automation systems.Results. Automated installation of accumulator water appointment for mechanization and automation of supply of small livestock farms or other objects with the consumption of water up to 30 m3/h. Compact units compared to the tower allows you to mount them in one of the production facilities, which significantly reduces the cost of construction and installation. Obligatory condition of normal operation of the installation of the accumulator is uninterrupted power supply facility. Maximum hourly water consumption at the facility should not exceed the pump in the working area. As intake device crazy water pumping systems using tube wells (borehole for Electropump units), or open water, mining and tube wells (for console centrifugal pumps).ConclusionsThe resulting technological and schematic diagrams of crazy automatic lifting installation type clause for lifting water from open reservoirs and wells mine from shallow to 5 m. The pressure in on and off contact pressure sensors.